The relationship between short- and long-distance swimming performance and repeated sprint ability - Meckel, Y.; Bishop, D. J.; Rabinovich, M.; Kaufman, L.; Nemet, D.; Eliakim, A. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to determine indices of repeated sprint ability (RSA) during a repeated sprint swimming test (RST), to compare these with previous similar running and cycling RST, and to correlate these indices with the best short (100 m, as an index of anaerobic performance) and long (2,000 m, as an index of aerobic performance) distance swimming times in 20 elite, national team level, male swimmers. Indices of RSA included the ideal sprint time (IS), the total sprint time (TS), and the performance decrement (PD) recorded during an 8 × 15-m swimming RST. The PD during the present swimming RST (4.7 ± 2.3%) was similar to that in previous running or cycling RSTs. However, the physiological responses after the swimming RST (heart rate 168 ± 7 b/min and blood lactate concentration 5.5 ± 2.0 mmol/L) were lower than typical responses after running or cycling RSTs. There was no significant relationship between any of the RST performance indices and either the 100-m or 2,000-m swimming results. Multiple regression analysis indicated that the 3 RST indices (IS, TS, and PD), contributed 36% of the variance of the 2,000-m, but not the 100-m, swimming time. A strong correlation was found between the 100- and 2,000-m swim times (r = 0.74, p < 0.05). The results suggest that RSA in swimmers is a specific quality that cannot predict short- or long-distance swim performance. The significantly strong relationship between the 100- and 2,000-m swim times is unique for swimming.